2015
DOI: 10.11646/zootaxa.4048.1.1
|View full text |Cite
|
Sign up to set email alerts
|

<strong>The trap-jaw ant genus <em>Odontomachus</em> Latreille (Hymenoptera: Formicidae) from Sumatra, with a new species description</strong>

Abstract: The ant genus Odontomachus Latreille is reviewed for Sumatra, the sixth largest island in the world and located in western Indonesia. Previously three species were recorded from the island: O. simillimus F. Smith, O. rixosus F. Smith, and O. latidens Mayr. We add two species to the fauna, O. procerus Emery stat. nov and Odontomachus minangkabau sp. nov. The new species belongs to O. rixosus species group, and it is morphologically most similar to O. rixosus and O. pararixosus Terayama & Ito. However, it can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 11 publications
1
25
0
5
Order By: Relevance
“…However, we found little support for the role of geographical distance as a primary regulator of Odontomachus macroevolutionary dispersal and distribution. Moreover, we found a strong distributional delimitation at Wallace's Line, which is in partial agreement with the hypothesis of biotic interactions (e.g., competition among closely related taxa) influencing geographical distribution (Wilson, ); the Oriental rixosus group dominates on the western side of the Wallace's Line, whereas the Indo‐Pacific clade dominates on the eastern side (Satria et al., ; Sorger & Zettel, ). In other insects, however, it has been reported that the Wallace's Line has been highly permeable, given the strong dispersal abilities of winged animals (e.g., Balke et al., ; Condamine et al., ; Matos‐Maraví et al., ; Müller, Matos‐Maraví, & Beheregaray, ; Tänzler, Toussaint, Suhardjono, Balke, & Riedel, ), and perhaps due to the continual turnover of species (i.e., immigration rate minus extinction rate) across geographically close islands, as expected by equilibrium theory (Gillespie & Roderick, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, we found little support for the role of geographical distance as a primary regulator of Odontomachus macroevolutionary dispersal and distribution. Moreover, we found a strong distributional delimitation at Wallace's Line, which is in partial agreement with the hypothesis of biotic interactions (e.g., competition among closely related taxa) influencing geographical distribution (Wilson, ); the Oriental rixosus group dominates on the western side of the Wallace's Line, whereas the Indo‐Pacific clade dominates on the eastern side (Satria et al., ; Sorger & Zettel, ). In other insects, however, it has been reported that the Wallace's Line has been highly permeable, given the strong dispersal abilities of winged animals (e.g., Balke et al., ; Condamine et al., ; Matos‐Maraví et al., ; Müller, Matos‐Maraví, & Beheregaray, ; Tänzler, Toussaint, Suhardjono, Balke, & Riedel, ), and perhaps due to the continual turnover of species (i.e., immigration rate minus extinction rate) across geographically close islands, as expected by equilibrium theory (Gillespie & Roderick, ).…”
Section: Discussionsupporting
confidence: 89%
“…The trap‐jaw ant genus Odontomachus has recently been the subject of taxonomic reviews (Fisher & Smith, ; MacGown, Boudinot, Deyrup, & Sorger, ; Satria, Kurushima, Herwina, Yamane, & Eguchi, ; Sorger & Zettel, ; Yoshimura, Onoyama, & Ogata, ) and higher‐level molecular systematic studies (Larabee et al., ). Odontomachus is a monophyletic genus comprised of 68 valid extant species (AntWeb, ; Satria et al., ; Schmidt & Shattuck, ), which are unevenly distributed across continents. The Oriental region (i.e., tropical and subtropical East Asia extending through the Malay Archipelago region west to the Wallace's Line) and the Australasian region (i.e., the Malay Archipelago region east of Wallace's Line and Australia) together harbour the largest number of Odontomachus species, with 31 valid taxa.…”
Section: Methodsmentioning
confidence: 99%
“…Morphological terminology follows mainly Brown (1976) and Satria et al (2015) with a few modifications (mostly syntactical), and Boudinot (2013) and MacGown et al (2014) for male genitalia. All measurements are given in millimetres (mm).…”
Section: Morphological Examination and Imagingmentioning
confidence: 99%
“…Petiole height, measured as maximum height of petiole in lateral view, perpendicular to petiole length, from an imaginary line tangential to petiolar apex to ventral surface of postpetiolar helcium, where the latter inserts into the petiole. Note: PTH here is measured only to the ventral surface of the postpetiolar helcium, instead of the ventral-most point of the subpetiolar process sensu MacGown et al 2014and Satria et al (2015). This is to ensure fair comparisons of PTH with O. malignus specimens (or their images), including the holotype, that are mounted such that the subpetiolar process is obscured or not measurable.…”
Section: Pthmentioning
confidence: 99%
“…Serangga memiliki peranan yang penting di alam, baik yang berdampak positif maupun negatif. Peranan positif serangga adalah sebagai polinator atau penyerbuk (Andrian & Maretta, 2017), sebagai dekomposer atau pengurai (Hasyimuddin et al, 2017), sebagai predator atau parasitoid (musuh alami) (Moningka et al, 2012;Satria et al, 2015;Satria et al, 2017), sebagai penghasil bahan-bahan berguna dan bermanfaat (Asthami et al, 2016), serangga memiliki kemampuan merespon perubahan yang terjadi pada lingkungan, sehingga potensi serangga sebagai bioindikator sangat diperhitungkan (Lach et al, 2010;Riyanto, 2016;Basna et al, 2017). Sedangkan peran negatif serangga di bidang pertanian dan kehidupan adalah sebagai hama (Fakhrah, 2016), sebagai vektor penyebab penyakit pada tanaman (Balfas et al, 2002) dan pada manusia (Meilin dan Nasamsir, 2016 (Pittendrigh, 1974).…”
Section: Pendahuluanunclassified